2018
DOI: 10.21315/tlsr2018.29.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Use of Pleurotus eous Strain P-31 Spent Mushroom Compost (SMC) as Soil Conditioner on the Growth and Yield Performance of Capsicum annuum L. and Solanum lycopersicon L. Seedlings under Greenhouse Conditions in Ghana

Abstract: The objective of this study was to investigate the influence of spent mushroom compost of Pleurotus eous strain P-31 on the growth and yield performance of pepper and tomato seedlings under greenhouse conditions. Sandy loam soil was combined with different percentages of SMC to obtain the following combinations (0, 5, 10, 15, 20, 25 and 30) %. Lower concentrations SMC5, SMC10 and SMC15 promoted vegetative growth (plant height, leaf area, chlorophyll content, number of leaves and axillary branches) of the two t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…Similar findings have been previously reported by Eudoxie and Alexender [70] in the use of spent mushroom substrate as a transplant media replacement for commercial peat in tomato production. Wiafe-Kwagyan and Odamtten [71] reported that SMS contained dry matter, crude protein, cellulose, lignin, NDF, and ADF (calcium, potassium, nitrogen, and sodium) which could influence the dry matter of test plants.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings have been previously reported by Eudoxie and Alexender [70] in the use of spent mushroom substrate as a transplant media replacement for commercial peat in tomato production. Wiafe-Kwagyan and Odamtten [71] reported that SMS contained dry matter, crude protein, cellulose, lignin, NDF, and ADF (calcium, potassium, nitrogen, and sodium) which could influence the dry matter of test plants.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Naveed et al (2018) reported that the use of organic waste from the agricultural industry may support the growth and bioavailability of Zn in corn plants. According to Kwagyan and Odamtten (2018), the use of mushro om waste compost with a ratio of 10% SMC and 90% soil was the best medium for supporting optimum vegetative growth in tomato and pepper plants. It was also (Spent Mushroom Compost.…”
Section: Potential Use Of Waste As Organic Fertilizermentioning
confidence: 99%
“…The current state‐of‐the‐art research shows the usage of fungal biotechnology in other fields such as restoration of damage environments (mycorestoration), via mycofiltration (i.e., use of mycelia to filter water), mycoforestry (i.e., use of mycelia to restore forest), mycoremediation (i.e., use of mycelia to ameliorate heavily polluted soils), myconuclear bioremediation (i.e.,use of mycelia to sequester soil of radioactive materials), mycopesticide (used as biopesticide to control pests), and also spent compost could be used as biofertilizer to enhance the fertility of the soil (Adenipekun & Lawal, 2012; Kortei et al., 2018; Stamets, 2005; Wiafe‐ Kwagyan & Odamtten, 2018; Wiafe‐Kwagyan et al., 2016). These instances represent fungal ability to restore the ecosystem where there are no adverse effects after fungal application.…”
Section: Introductionmentioning
confidence: 99%